Pengaruh Suplemen Omega-3 terhadap Marker Peradangan pada Pasien Kanker Kolorektal: Laporan Kasus Berbasis Bukti: Laporan Kasus Berbasis Bukti - Octavia M, Vanessa Aryani; Andayani, Diyah Eka (PT Kalbe Farma Tbk., 2026)
Introduction: Omega-3 polyunsaturated fatty acids (PUFAs), particularly eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), have immunomodulatory and anti-inflammatory effects that may help reduce inflammatory markers such as interleukin-6 (IL-6) andC-reactive protein (CRP) in colorectal cancer (CRC) patients. Methods: A literature search was conducted in PubMed, Cochrane Library, and Google Scholar from May to June 2025. Included studies were meta-analyses or randomized controlled trials (RCTs) evaluating omega-3 supplementation in adult CRC patients, with inflammatory markers as primary outcomes. Critical assessment tools and levels of evidence of the final articles are based on the Oxford Centre for Evidence-Based Medicine. Results: Three meta-analyses were reviewed. Omega-3 supplementation was given orally (660 mg–4.8 g/day) or parenterally (0.1–0.2 g/kg/day) for 5 to 84 days. IL-6 and tumor necrosis factor-α (TNF-α) levels were significantly reduced in most studies. CRP showed modest and inconsistent improvement, whilealbumin slightly increased. High heterogeneity in dose, timing, and administration routes limited the strength of interpretation. Conclusion: Omega-3 supplementation appears to reduce systemic inflammation in CRC patients, particularly through IL-6 suppression. Although the effect on CRP is inconsistent and albumin improvement is mild, these findings suggest a potential benefit in inflammatory and nutritional status. Further standardized and high-quality RCTs are needed to confirm clinical utility and optimal dosing strategies.